Role of the nuclear receptor Tailless in adult neural stem cells - Wang, Yu; Liu, Hai-Kun; Schütz, Günther (Mechanisms of development, 2013)
Tailless (Tlx) is an orphan nuclear receptor which is specifically expressed in the neural stem cells of the two largest germinal neurogenesis zones in the adult mouse brain, the subventricular zone (SVZ) of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus. By interacting with its cofactors, Tlx represses its target genes and plays an important role in the maintenance of adult NSCs. This review provides a snapshot of current knowledge about Tlx function in adult NSCs.